Fertility and productivity of ricefield for integrated rice-fish farming in mid-hills of Nepal - Wagle, Suresh Kumar; Mulmi, Raja Man; Gurung, Tek Bahadur; Lamsal, Gopal Prasad (Journal of Natural History Museum, 2008)
Physical and chemical parameters of water will determine species that can survive in ricefields. Fertility and primary productivity are important in rice-fish farming because they affect food availability for fish. Fish in ricefields feed extensively on the aquatic invertebrates and detrital aggregate. The effect of fertilization practices on physico-chemical properties and abundance of such aquatic fauna in rice-field is largely undocumented. Water quality parameters affecting fertility and productivity of rice-fish farming were studied for dry and wet season rice in Tupche, Nuwakot and Khudi of Kaski during March 2000 and November 2001. Parameters were obtained for irrigated rice-fish fields to assess the effect of organic and inorganic fertilizer on water quality, population dynamics of aquatic invertebrates and, rice and fish yield. Key words: Rice-fish; fertilization, water quality; ecosystem; zooplankton J. Nat. Hist. Mus. Vol.22, 2005 p.1-21